2020
DOI: 10.1111/cod.13644
|View full text |Cite
|
Sign up to set email alerts
|

Occupational airborne contact urticaria, anaphylaxis and asthma in farmers and agronomists due to Bruchus pisorum

Abstract: Background: Occupational contact urticaria due to inhalation of legume pest allergens has rarely been described. Objective: To determine the cause of an outbreak of airborne contact urticaria, asthma, and anaphylaxis in farmers and agronomists studying the disinsectization of dried peas. Peas were treated with aluminum phosphide (EPA). Methods: Extracts prepared from Bruchus lentis and Bruchus pisorum bodies and from healthy legumes, EPA-treated legumes, and infested legumes, were used for in vivo tests (skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Multiple recent case reports describe novel occupational CU triggers including diethyl phthalate in hand sanitizers among healthcare workers [ 70 ], indigo dye in natural hair dyes among hairdressers [ 71 ], pork among slaughterhouse workers [ 72 ], buckwheat among food handlers [ 73 ], and legume pests among farmers [ 74 ].…”
Section: Contact Urticaria and Protein Contact Dermatitismentioning
confidence: 99%
“…Multiple recent case reports describe novel occupational CU triggers including diethyl phthalate in hand sanitizers among healthcare workers [ 70 ], indigo dye in natural hair dyes among hairdressers [ 71 ], pork among slaughterhouse workers [ 72 ], buckwheat among food handlers [ 73 ], and legume pests among farmers [ 74 ].…”
Section: Contact Urticaria and Protein Contact Dermatitismentioning
confidence: 99%
“…Beetles can be pests in legumes, such as lentils and peas, where they are an occupational risk to the farmers, agronomists or even to the cooks preparing the food (Table 2) [35][36][37]. The use of extracts of non-infested legumes, infested legumes and the beetles Bruchus lentis or Bruchus pisorum in SPT and bronchial challenge tests could exclude allergy to the legumes themselves.…”
Section: Beetle Allergymentioning
confidence: 99%
“…The results showed a positive response to prick testing, provocation testing and immune detection to parasitic pea extracts and B. pisorum . The authors concluded that the entrance by inhalation or puncture of setae released by B. pisorum may be a cause of contact urticaria, anaphylaxis and asthma [21]. As regards nematodes, Anisakis simplex infests fishes and cephalopods, causing a number of clinical disorders, including occupational respiratory disease, dermatitis and anaphylaxis.…”
Section: Causes Of Airborne Anaphylaxismentioning
confidence: 99%